Manajemen Kegiatan Keagamaan Generasi Remaja (Genre) dalam Pencegahan Stunting di Kota Binjai - Apriliani, Putri; Sampurna, Ahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research discusses the Religious Activities of the Youth Generation (GenRe) in Stunting Prevention. The purpose of this research is to determine the Management of Religious Activities of the Youth Generation (GenRe) in Stunting Prevention. This research uses a descriptive method with a qualitative approach to field research. The data source in this research is direct information using interview, observation, and documentation data collection techniques. The results of this research show that in efforts to prevent stunting the Generation Youth (GenRe) community uses. The management function is POAC (Planning, Organizing, Actuating, Controling). Planning in religious activities at GenRe is by providing understanding to the prospective bride and groom about pre-wedding so that they understand how to provide good nutrition to their babies whether they are still in the womb or born. At the Organizing stage, what the GenRe Binjai community carried out was in the form of preparing an organizational structure and dividing tasks into their respective fields. Actuating (implementation) implemented by GenRe is in the form of teaching, habituation, and motivation given by the GenRe chairman to the members. Controlling (evaluation) at this stage is carried out once a year by the head of GenRe.